Zambian policy-making and the donor community in the 1990s - Hendrik vander Heijden (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The move towards multiparty democracy in Zambia in the early 1990s was heralded as the beginning of a new era of more pluralist politics in Africa. The new government's willingness to adopt economic reforms and policies, hitherto resisted, was also seen as a sign that henceforth African governments would be willing to `own' reforms. A decade later, the optimism seems unjustified. The political reforms floundered, while economic adjustment proved to be much slower than the earlier signs had indicated. Growth ground to a halt and poverty increased in this once rich country. The country's overall dependency on aid increased as well. To increase reform ownership in Zambia, there is need to shift some of the burden of behaviour during adjustment to the government, not just donors. There is scope for the government to take more responsibility for its reforms, including the internal mobilisation of resources for investment. Ultimately, policies enforced from outside will only lead to policy reversal when the conditonalities are removed. – Zambia ; resource booms ; economic reforms ; policy reversal
Keywords: O10; O20; O55; P26; Q33; Q38; 330; Entwicklung; Entwicklungspolitik; Entwicklungshilfe; Erschöpfbare Ressourcen; Sambia